Availability of ICT Resources for the Research and Supervision Process: Perspectives from the Supervisors' and Supervisee Experiences of Public and Private Universities of Khyber Pakhtunkhwa, Pakistan - Sadaf Bano; Dr. Safdar Rehman Ghazi; Sanober Bano, (Dialogue Social Science Review (DSSR), 2025)
A study aimed to investigate the availability of ICT resources for the research and supervision process: perspectives from the supervisors' and supervisees' experiences of public and private universities of Pakistan. It investigates how public and private university supervisors and supervisees perceive the availability of ICT resources, particularly in terms of hardware, software, and Internet tools. A mixed-methods embedded design (quantitative and partially qualitative) was adopted. The researcher selected a survey design, and the population comprised all supervisors and supervisees enrolled in the academic year 2021-2023 at Khyber Pakhtunkhwa University. A sample of 396 participants was selected using a systematic sampling technique. Quantitative data were collected through structured questionnaires, while the researcher obtained qualitative insights through open-ended responses. Data were analysed using SPSS-26, applying descriptive and inferential statistical techniques, including Mean, Standard Deviation, and Cohen's d. Thematic analysis was applied to the qualitative data to gain deeper insights into ICT resource integration. Key findings indicated that ICT tools and resources were frequently available in the research process based on the experiences of supervisors and supervisees in both public and private universities. Thematic analysis further revealed that additional ICT tools beyond those listed in the structured instruments were also available, as highlighted by qualitative responses from both groups. Hypothesis testing showed no significant differences between public and private universities regarding ICT availability, except for hardware.